1995
DOI: 10.1095/biolreprod53.6.1243
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Progesterone and Estradiol Production by Mouse Cumulus and Mural Granulosa Cells by a Factor(s) Secreted by the Oocyte

Abstract: Mouse oocytes secrete a factor(s) that inhibits progesterone and enhances estradiol production by cumulus granulosa cells. The purpose of this study was to investigate the mechanisms by which the production of these steroids is modulated. Mouse oocyte-cumulus cell complexes (intact) and complexes from which the oocytes were removed microsurgically (oocytectomized; OOX) were cultured for up to 48 h in the presence of FSH (150 ng/ml) and testosterone (5 x 10(-7) M). For these experiments, all cells were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 46 publications
2
80
0
2
Order By: Relevance
“…However, there are several in vitro studies suggesting progesterone as a spermattractant candidate. After ovulation, the cumulus cells secrete progesterone (Vanderhyden & Tonary 1995, Chian et al 1999, Yamashita et al 2003, Guidobaldi et al 2008, which may form a concentration gradient by diffusion along and beyond the cumulus matrix (Teves et al 2006, Guidobaldi et al 2008, Oren-Benaroya et al 2008. A gradient of a picomolar concentration of progesterone chemoattracts only capacitated spermatozoa, those ready to fertilize the egg (Teves et al 2006).…”
Section: Sperm Guidance Mediated By the Ovulation Productsmentioning
confidence: 99%
“…However, there are several in vitro studies suggesting progesterone as a spermattractant candidate. After ovulation, the cumulus cells secrete progesterone (Vanderhyden & Tonary 1995, Chian et al 1999, Yamashita et al 2003, Guidobaldi et al 2008, which may form a concentration gradient by diffusion along and beyond the cumulus matrix (Teves et al 2006, Guidobaldi et al 2008, Oren-Benaroya et al 2008. A gradient of a picomolar concentration of progesterone chemoattracts only capacitated spermatozoa, those ready to fertilize the egg (Teves et al 2006).…”
Section: Sperm Guidance Mediated By the Ovulation Productsmentioning
confidence: 99%
“…Data are described as median (range). a p < 0.05 compared to <35; b p < 0.05 compared to [35][36][37][38][39] …”
Section: Discussionmentioning
confidence: 99%
“…Although not fully defined yet, cumulus GCs express characteristics distinct from mural GCs, which are steroidogenically more active [37,38]. Cumulus cells communicate with each other and with the oocyte through specialized gap junctions that allow metabolic exchange and transport of signaling molecules for appropriate follicular development [35,36,39].…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone is presumably responsible for the stimulation of sperm motility by the PACAP-treated fluid because an increased amount of progesterone was detected when the cumulus-oocyte complexes were treated with PACAP. Studies have demonstrated that human, mouse, porcine, and rabbit cumulus cells synthesize and secrete progesterone (Osman et al 1989, Vanderhyden & Tonary 1995, Chian et al 1999, Yamashita et al 2003, Guidobaldi et al 2008. In addition, human sperm express a cell surface receptor for progesterone (Luconi et al 2004).…”
Section: Discussionmentioning
confidence: 99%